(untitled) (Economic and Political Thought, 2016)
Former expectations related to free movement of people within the EEA can be, at least partially, in question. The article aims at highlighting basic trends in migration outflows of Poles to Norway, with special attention paid to the integration challenges, and in particular the integration of Polish children in Norway. Increasingly, more Poles decide on a more permanent settlement instead of shuttling between Norway and Poland. It is a challenge not only for them but also for the Norwegian society and policy in particular. The article is a result of the TRANSFAM project, funded by the Norway Grants, which is focused on studying transnational migrations and starting families by Poles in Norway. The project participants are the Jagiellonian University (leader) and its partners from the Polish-Norwegian consortium: the Centre for International Relations, Agder Research and Nova.